Абстрактні іменники у реєстрі Зведеного словника - Тименко, Л.О. (Лексикографічний бюлетень, 2013)
In the article the abstract nouns Ukrainian language in diachronic perspective and question their current operation. The analysis of fixation abstract nouns Ukrainian language-XHI XIX century. Allowing us to understand the nature of the evolution of modern Ukrainian abstract vocabulary.